Additive engineering mechanisms for antimony chalcogenide solar cells - Sutton, Matthew (The University of Edinburgh, 2025)
Antimony chalcogenide solar cells are an attractive thin film solar technology with a tuneable bandgap, high inherent stability and a large absorption coefficient. They are often solution processed, allowing for the easy employment of chemical additives. Though many additives have already been utilised, the underlying chemical mechanisms are often poorly understood. The formation of unwanted side phases, most notably Sb₂O₃, are also largely not understood. Here, the chemical mechanism of an additive of proven efficacy, EDTA, is investigated through the use of NMR spectroscopy and a solution-based chemical aggregation test, as well as the use of various techniques including powder-XRD, SEM and Raman spectroscopy on Sb₂O₃ films formed using EDTA. These tests demonstrated that EDTA can control the deposition of Sb₂O₃ films, while suppressing the formation of the undesired Sb₂O₃ side-phase. The solution-based chemical aggregation test was further developed into a screening process to find additives which rival and exceed EDTA. After the discovery of successful additives using this screening process, a chemical mechanism for the suppression of Sb₂O₃ formation was found by correlating improvement of solar cell performance with the pH of the additive. The mechanism proposed in the literature for the control of film deposition by EDTA was that through the sequestration of Sb³⁺, EDTA was effectively changing the deposition mechanism from per-nanoparticle to per-ion deposition, thus forming more compact and large crystal grains. By relating the capability of an additive to bind Sb³⁺ to its relevant solar cell performance, this mechanism is further evidenced and expanded. The deeper understanding of these additive mechanisms afforded by this investigation will allow for more focussed and informed development of additives for efficient antimony chalcogenide solar cells in the future, particularly those using a benign and abundant TiO₂ electron transport layer.
Keywords: Photovoltaic; Antimony Chalcogenide; Material Science; Chemistry; Chemical Engineering; Mechanism